Entre o prazer e o sofrimento: histórias de vida, drogas e trabalho - Fernanda Tarabal Lopes (2013)
This thesis had as it core objective to retlect on the existing relationship between work and addiction. Therefore, a study was carried out having as its fundamental empirical condition to restore the life story of four individuals: alcohol and other controlled substances addicts and workers. The threshold of this research was based upon the establishment of a meaning to the drug addiction phenomenon and its relation to labor. ln general, the traditional approaches on the alcohol and drug intake narrows the problem down to va domestic level, not taking into account the primacy of the political dimension which Hts the job. Thus considering labor as a human constructingcondition and its role in a mans life. This activity is further understood for the richness and complexity of its dynamic, which can be configured either as a source of pleasure or a source of suffering or both. To understand the addiction this investigation was based on the psychoanalytic theory, where concepts relating to the psychic comprehension of the intoxication process were recovered. To understand labor, the study had as reference, concepts coming from the working · psychodynamics, in which the relationship between man and labor and the concept of public space are discussed. lt has been concluded that the working sphere and controlled substance addiction are directly overlapped and that understanding of one of them would give meaning to the other one and vice versa. However, the meaning established by the subjects in this relationship is private, because they relate to unique experiences and subjectivities built by each one of them and their life experiences. lt was also found out that in order to understand the subject at work it is necessary to be aware of their individual circumstances. Finally, it is necessary to look at him in his singularity and in his human and psyche conditions. Concerning the study on the controlled substance users it is vital to mention its centrality and primacy, whether in the construction of its subjectivity, whether concerning his role in society, whether as a citizen and worker.